Bullying and Cyberbullying: Their Legal Status and Use in Psychological Assessment - Muthanna Samara (11619435) (2017)
Bullying and cyberbullying have severe psychological and legal consequences for those involved. However, it is unclear how or even if previous experience of bullying and cyberbullying is considered in mental health assessments. Furthermore, the relevance and effectiveness of current legal solutions has been debated extensively, resulting in a desire for a specific legislation. The purpose of this study is to investigate the psychological and legal components of bullying and cyberbullying. This is a qualitative research that includes interviews with five practitioner psychologists and four lawyers in the United Kingdom (UK). Thematic analysis revealed three main themes. One theme is related to the definition, characteristics, and impact of bullying and cyberbullying and the need for more discussion among the psychological and legal professions. Another theme is related to current professional procedures and the inclusion of questions about bullying and cyberbullying in psychological risk assessments. The third theme emphasised the importance of intervention through education. Two key messages were highlighted by the lawyers: ample yet problematic legislation exists, and knowledge will ensure legal success. The study recommends the necessity of performing revisions in the clinical psychological practices and assessments, and the legal policies regarding bullying and cyberbullying. In addition to improving legal success, this will reduce bullying prevalence rates, psychological distress, and psychopathology that can be comorbid or emerge as a result of this behaviour. Other Information Published in: International Journal of Environmental Research and Public Health License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijerph14121449